Aerosol Characterization over a High Altitude Location in Central Himalayas - Pant, P (Journal of the Institute of Engineering, 2012)
Our climate is strongly influenced by the manner in which solar radiation is absorbed and scattered in the Earth’s atmosphere. Atmospheric aerosols play an important role in modifying the radiation budget of the earth-atmosphere system. Aerosols have a direct impact on the atmosphere as they scatter and absorb solar and infrared radiations and indirectly affect the size distribution of cloud droplets. Hence, the knowledge of aerosols’ characteristics is the basic requirement for understanding the impact of aerosols on our environment. In order to delineate the optical and physical properties of aerosols, the collocated measurements of aerosols are carried out at Manora Peak (29.36 N; 79.45 E, altitude ~ 1960 meters), Nainital: a high altitude location in central Himalayas. Since the observing site is located geographically in the free troposphere, thus the aerosol measurements from such a region have the importance for providing a sort of background level of aerosol-parameters against which the impact of aerosol-loading from far-off low laying regions can be assessed. The retrieved parameters of aerosols at ARIES are comprised of aerosol optical depth, mass/number concentrations of composite aerosols, BC mass concentration, total suspended particulate matter, total columnar ozone and water vapor content, meteorological parameters, traces gases etc. The analyzed results have been summarized in the present talk. DOI: http://dx.doi.org/10.3126/jie.v8i3.5935 JIE 2011; 8(3): 87-93